Metal-coordination driven intramolecular twisting: a turn-on fluorescent-redox probe for Hg2+ ions through the interaction of ferrocene nonbonding orbitals and dibenzylidenehydrazine. Issue 23 (15th May 2019) - Bhatta, Sushil Ranjan; Mondal, Bijan; Lima, Sudhir; Thakur, Arunabha
Abstract : A unique C 2 symmetric azine bridged bi-ferrocenyl receptor has been designed and synthesized for the selective detection of Hg 2+ ion with a low detection limit as 15 nM via turn on fluorescence with a blue shift. Abstract : A unique C 2 symmetric azine bridged bi-ferrocenyl receptor (4 ) has been modelled and synthesized. In this work, we are able to synthetically regulate conjugation of the dibenzylidenehydrazine fluorophore unit to unexpectedly reveal metal-coordination driven intramolecular twisting. The present probe shows a dramatic turn-on fluorescence response with 91 fold increment of quantum yield along with 17 nm blue shift upon binding with Hg 2+ ions selectively with a limit of detection as low as 15 nM. Upon Hg 2+ recognition, the ferrocene/ferrocinium redox peak was anodically shifted by Δ E 1/2 = 78 mV, indicating the formation of a new complex species. A plausible binding mode of Hg 2+ ions with compound4 has been proposed based on 1 H NMR titration, a high-resolution mass spectrometry (HRMS) study and a density functional theory (DFT) study along with the Job's plot analysis. Interestingly, DFT calculations have revealed that the reason for fluorescence enhancement after coordination to Hg 2+ ions is not due to conventional restricted CN isomerization or interrupted N–N single bond rotation rather it is due to the increase of the π ← π* transition at the expense of the n → π* (aromatic) transition of the free ligand. Furthermore, TD-DFT calculations of the first excited singlet state of4 and [4 ·Hg 2+ ] revealed the involvement of the aromatic π electrons with the vacant site of Hg 2+ ions which may be further attributed to the fluorescence enhancement phenomenon. In addition, receptor4 was successfully applied for the detection of Hg 2+ ions in real samples.